Evaluation of wood-based coating performance for ultraviolet roller and conventional air-atomization processes - Hazir, Ender; Huseyin Koc, Kucuk (Maderas. Ciencia y Tecnología, 2021)
In this study, the effects of two different coating processes on the surface coating performance of wood-based panels were investigated. The samples were prepared using an ultraviolet (UV) roller coater and conventional air-atomized systems. Adhesion strength, surface coating hardness, and layer thickness were selected as the coating performance parameters. These coating performance parameters were analyzed using an analysis of variance (ANOVA), Grubb’s test, and probability plot. Adhesion strength, surface coating hardness, and layer thickness were measured using the pull-off test, pendulum hardness, and ultrasonic layer thickness, respectively. According to the ANOVA results, the coating process type was the most significant